Medieval Wisdom and Modern Diagnosis: A 9th-Century Physician’s OCD Description vs. ICD–11 - Usman Abdul-Quayum; Suleman Jehanger; Imran Ali (BJPsych Open, 2025)
Aims: This study explores the historical roots of Obsessive–Compulsive Disorder (OCD) through an analysis of a ninth-century treatise Sustenance of the Soul by Abu Zayd al-Balkhi. It aims to compare al-Balkhi’s descriptions and treatments of OCD with the modern-day classification and understanding of ICD–11. We hypothesise that al-Balkhi could offer a more nuanced, holistic understanding of OCD, including recognition of its physical, psychological, and social aspects, and that this historical perspective can offer valuable insights into current psychiatric practices.